Peran dan Strategi Laznas Nurul Hayat Kantor Cabang Madiun dalam Mengentaskan Masalah Perekonomian - Ummah, Novita Hanivatul (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2021)
This study aims to examine the role and strategy of The Branch of LAZNAS Nurul Hayat based in Madiun that alleviating economic problems. In Islam, apart from being zakat, donations and alms are also effective solutions to poverty alleviation. Therefore we need zakat, infaq and alms management body that has a good management mechanism. It also has an optimal role in efforts to improve the economy of the community. The LAZNAS Nurul Hayat in Madiun formed in order to maximize zakat management and maximize the increase of the economy sector for the people in the Madiun area. The results of this study indicate that the existing zakat management mechanism of LAZNAS Nurul Hayat Madiun Branch is good enough. The role of zakat, infaq and alms is an effort  to improve the economy for people in the Madiun area that  form of consumptive assistance and productive assistance. Its implementation is based on Islamic law and law.